The use of VARI, GLI, And VIgreen formulas in detecting vegetation in aerial images - Eng L.S.; Ismail R.; Hashim W.; Baharum A. (Faculty of Engineering, Universitas Indonesia, 2023)
Vegetation monitoring is a task that requires much time and human effort, but by using an unmanned aerial vehicle with a system that can store captured data digitally, the task can be more manageable and efficient. Past research has shown many formulas were developed by researchers to capture vegetation data in varying conditions and equipment. This paper discusses an experiment conducted to test three of those formulas using visible band data images. The formulas are the visible atmospherically resistant index, the green leaf index, and the visible atmospherically resistant indices green. The objective of this paper is to report and discuss our findings from experiments conducted using each formula as well as to compare the accuracy of these formulas. IJTech 2019.